Efeitos da hiperoxia sobre a concentração de lactato e perfil oxidativo de corredores de endurance - Araújo, Gianlucca De Lima (2023)
The aim of this study was to verify whether endurance runners, when breathing a high concentration of oxygen (FIO2 = 99.5%), present blood changes in lactate production that could impact the second threshold, as well as to investigate the deleterious effects on the inhalation of high concentrations of oxygen (hyperoxia) on parameters of oxidative stress in blood samples from runners. The study group consisted of 08 male amateur runners, Endurance runners, healthy and physically active, aged 33.40 ± 8.11 years, body mass 73.21 kg ± 6.30 and height 175.88 ± 5.36 cm. The volunteers were submitted to two maximum effort tests – 1 hyperoxia situation; 2 in normoxia. Mader's progressive protocol was the test of choice, where the initial test speed was determined at 9.0 km/h, with an increment of 1.8 km/h every 5 minutes (stage). The following variables were collected: - heart rate (HR), blood pressure (BP), blood glucose (Glc) and blood lactate (Lac), oxygen saturation (SPO2) and subjective sensation on exertion (SSE). Blood collections for analyzing the oxidative profile of the runners were performed from venipuncture, collecting a total of 8 ml of blood, used for the evaluation of oxidative stress parameters such as: levels of protein thiols (PSH) and lipid peroxidation (malondialdehyde , MDA). We found no statistical difference in athletic performance, HR and SSE during running, and in Lac concentration during the initial stages of the test. It was found that during recovery, HR in hyperoxia situation was significantly higher (115.63 ± 11.83, p≤0.0002). Blood pressure was not significantly different in hyperoxia. Our data demonstrated that there was a lower response of the blood Lac concentration in hyperoxia in the last two submaximal stages (2.55 ± 2.04, p≤0.0075 and 3.66 ± 2.17, p≤0.0048) and during the third stage of recovery (p≤0.05 ). As for blood analysis, it was found that at rest and recovery in both conditions, the MDA concentration was not statistically significant. However, the PSH content was significantly higher in a hyperoxic situation during recovery compared to rest (147.50 ± 8.60, p≤0.046). We conclude that for Endurance runners, the hyperoxia condition does not increase performance or substantially influence the HR, but acts considerably on the lower production of Lac, establishing changes in the curve. Hyperoxia, under these conditions of protocol and exposure time, was not harmful to the point of triggering lipoperoxidation during dynamic progressive exercises, however it was an antioxidant in relation to the increase in protein thiols found in the serum of these runners.